Predictors of ISUP score upgrade in patients with low-risk prostate cancer. Issue 3 (June 2021) - Haberal, Hakan Bahadir; Artykov, Meylis; Hazir, Berk; Citamak, Burak; Altan, Mesut; Yazici, Sertac; Akdogan, Bulent; Ozen, Haluk
Introduction: The literature contains few studies that focus on the relationship between International Society of Urological Pathology (ISUP) score upgrade and complete blood count (CBC) parameters for patients with low-risk prostate cancer and studies achieved inconclusive results. Methods: We retrospectively analyzed our institutional database for patients with prostate cancer who underwent radical prostatectomy (RP) between 1994 and 2017. In total, we included 633 patients with low-risk prostate cancer in the study. We investigated the effects of clinicopathologic factors on ISUP score upgrade. Moreover, we compared RP pathologic outcomes between the patients with and without ISUP score upgrade. Results: The mean age and follow-up periods were 61.09±6.61 years and 41.9±1.8 months, respectively. ISUP score upgrade was observed in 207 patients (32.7%). In multivariate analysis, high prostate-specific antigen (PSA) density and percentage of positive cores were found to be significantly associated with ISUP score upgrade ( p = 0.003 and p = 0.003, respectively). The neutrophil–lymphocyte ratio, platelet–lymphocyte ratio, monocyte–lymphocyte ratio, and eosinophil–lymphocyte ratio were found to have no effect on ISUP score upgrade ( p = 0.856, p = 0.353, p = 0.128, and p = 0.074, respectively). The percentage of tumors, surgical margin positivity, seminal vesicle invasion rate, and extraprostatic extension rate in RP pathology were higher in patients with ISUP score upgrade ( p < 0.001, p < 0.001, p < 0.001, and p < 0.001, respectively). Conclusions: Approximately one-third of the patients in our series had ISUP score upgrade in RP pathology. PSA density and the percentage of positive cores were found to be the factors significantly associated with ISUP score upgrade. CBC-related factors had no effect on ISUP score upgrade.